ASPIRASI PUBLIK SEBAGAI PONDASI PEMBENTUKAN UNDANG-UNDANG YANG BERKEADILAN - Nasya Oktavia (JURNAL ILMIAH NUSANTARA, 2025)
Abstract. The formation of equitable laws is a critical element in achieving an inclusive democracy that responds to the needs of society. This article examines the importance of public aspirations as the fundamental basis for justice-oriented legislation. Using a qualitative approach through a literature review, this study analyzes the role of public aspirations, barriers to public participation, and strategies to enhance public engagement in the legislative process. The findings reveal that public aspirations play a strategic role in enhancing the legitimacy and effectiveness of laws. However, challenges such as lack of transparency, elite dominance, and low public participation remain significant obstacles. To address these issues, strategic measures are proposed, including increasing transparency, developing technology-based public consultation platforms, providing legal education to citizens, and fostering multi-stakeholder collaboration. By optimally accommodating public aspirations, the legislative process will not only produce legitimate legal products but also strengthen social justice. This study highlights the importance of deliberative democracy as a framework to ensure that every law reflects the needs and expectations of society comprehensively. Keywords: Public Aspirations, Lawmaking Process, Social Justice, Public Participation, Deliberative Democracy